The absence : memoirs of a Banshee drummer - Budgie (Musician) (White Rabbit, 2025)
"Before he was Budgie, Peter Clarke was a boy growing up in working class St Helens in the 1960s. The loss of his mum at a young age created the absence that haunts the pages of this book. As a teenager disenchanted with art school in Liverpool, Peter became Budgie and befriended the likes of Jayne Casey, Pete Burns and other luminaries of the legendary Eric's Club before taking off for London and the big city heat of punk. Budgie's unique technique and musical sensitivity endeared him to the all-female group The Slits, who asked him to play on their debut album Cut. Subsequent touring with former members of the Sex Pistols and others from the post punk aristocracy firmly established Budgie's reputation for innovation. But the beating heart of this at times painfully honest account of a life often sabotaged is, of course, his long-term position as Siouxsie and the Banshees' drummer and co-writer alongside his ex-wife Siouxsie Sioux. Their creative partnership produced some of the most seductive and celebrated pop music of the decade. Eventually, their personal relationship started to fall apart, with inevitable consequences for both bands. The Absence is bravely unflinching in its dissection of how and why this happened, and powerfully moving in its account of the angels that emerged to heal both these wounds and those of a mother's lost love. A man and musician whose creativity and singular style came to define the goth-pop 1980s, Budgie's life is both fabulously glamorous and a cautionary tale. For the first time the story of the era's most exalted and mysterious bands has been told by one who survived inside the belly of the beast."